THE DEEP NEURAL NETWORK-A REVIEW - Jawad, Eman (IJRDO -JOURNAL OF MATHEMATICS, 2023)
Deep neural networks are considered the backbone of artificial intelligence, we will present a review of an article about the importance of neural networks and their role in other sciences, their characteristic, networks architecture, types, mathematical definition of deep neural networks, as well as their applications.